Communist trade with developing countries, 1955-65 - Sawyer, Carole A. (New York : F.A. Praeger, 1966)
The major purpose of this study is to evaluate communist claims about their trade with developing economies and to analyze the most important facets of this trade.
Includes bibliographical references.
rpm 21/01/2019
Loans
Keywords: Communist countries; Developing countries